Media Literacy Education for Society in Facing Media Content in the Digital Age - Samsinar S.; Akbar Syamsuddin (Palakka : Media and Islamic Communication, 2020)
This study discusses the importance of media literacy education for the community, critical learning for the community about media content and selecting media content in obtaining effective and efficient information for the community. This research is a library research with a descriptive-qualitative approach. The method and analysis used is an inductive qualitative analysis. Inductive qualitative data analysis is an analysis based on the data obtained, then it is developed into an answer to the problems in this study, and the data is sought repeatedly so that the data collected can be known to be accepted or rejected. The results showed that media literacy education for the community is very important. Through media literacy education, it will affect the community both cognitively, affective and psychomotor, so that with this ability they are able to filter media content that is useless and not needed by them and ward off hoax news or sites. In understanding media literacy, society must also be critical in sorting, selecting, assessing and controlling the content of the media used. With critical learning, people are able to use the media wisely, ethically and responsibly with the media used. In addition, the public must also pay attention to strategies in creating messages or content in the media through message setting agendas, framing and semiotics. In selecting media content to obtain information effectively and efficiently, the public must be careful in utilizing the media. They must make the media a place to increase scientific insight, social transformation, and as entertainment. That way, the presence of the media has a positive effect on society to participate and make a constructive contribution to the mass media.